Clinical Recovery from CNS Damage - Naritomi, Hiroaki; Krieger, Derk W. (Karger, 2013)
After decades of focusing on how to alleviate and prevent recurrence of acute CNS injuries, the emphasis has finally shifted towards repairing such devastating events and rehabilitation. This development has been made possible by substantial progress in understanding the scientific underpinnings of recovery as well as by novel diagnostic tools, and most importantly, by emerging therapies awaiting clinical trials. In this publication, several international experts introduce novel areas of neurological reorganization and repair following CNS damage. Principles and methods to monitor and augment neuroplasticity are explored in depth and supplemented by a critical appraisal of neurological repair mechanisms and possibilities to curtail disability using computer or robotic interfaces. Rather than providing a textbook approach of CNS restoration, the editors selected topics where progress is most imminent in this labyrinthine domain of medicine.